KONSEP KEWAJIBAN MANUSIA DAN IMPLIKASINYA DALAM PENDIDIKAN ISLAM DAN KONSEP KERIDHAAN ALLAH (MARDHÄ€TILLÄ€H) SEBAGAI TUJUAN AKHIR PENDIDIKAN ISLAM - Pahrizal; Erihadiana, Mohamad; Ruswandi, Uus (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2023)
Multicultural education is education for all people without any distinction between one another, Islam as a religion that is Rahmatan Lil alamin which is passed down to humans also pays attention to this matter, Islam emphasizes that there is no difference between humans in the sight of Allah from a cultural aspect. This study aims to examine how the integration of multicultural education with the Koran program at Islamic boarding schools in the Koran village, Sumedang Jabar. The method used in this study is a qualitative research method with a descriptive approach which aims to describe how the form of integration of multicultural education with the Koran program by collecting data through observation, documentation, and interviews. As for the results of this study Multicultural education is as a sunnatullah an inevitability that cannot be avoided, there is no difference in human views of different races, cultures or religions and beliefs. At Islamic boarding schools, all students have the same educational rights as other students, regardless of those who are able or less fortunate, have high or low economic status, and do not differentiate between facilities, there is no difference, everyone gets the same as the others. Likewise, there is no difference because of ethnicity or language.